Hindu women's property rights in rural India - Patel, Reena (Aldershote, 2007)
This volume addresses the issue of Hindu peasant women's ability to effectuate the statutory rights to succession and assert ownership of their share in family land. The work combines a critical evaluation of law with economic analyses into allocation of resources within the family as a means of addressing gender relations and explaining resulting gender inequalities.
Keywords: "Women-Legal status,Laws etc"